Correlation Between Fitspiration Content, Physical Activity and Body Image Among Adolescents at SMPN 2 Cimalaka - Mahyati Mahyati; Dedah Ningrum; Rafika Rosyda (LPPM STIKes Muhammadiyah Ciamis, 2026)
This study examined the association between exposure to fitspiration content and physical activity and body image among adolescents at SMPN 2 Cimalaka. Using a quantitative correlational design with a cross-sectional approach, data were collected from 195 students aged 11 to 14 years through a validated questionnaire assessing fitspiration exposure, activity levels, and body image. The results indicated that exposure to fitspiration content was prevalent, with 86.7 percent of respondents reporting exposure. However, a substantial proportion of adolescents still reported low physical activity, accounting for 59.5 percent, and low body image satisfaction, accounting for 76.4 percent. Statistical analysis using the Chi-Square test found a significant positive association between fitspiration content exposure and physical activity, with a p-value of 0.001, suggesting a potential association with increased physical activity. However, fitspiration content exposure was not significantly associated with body image, as indicated by a p-value of 0.120, suggesting that factors beyond social media content play a more substantial role in shaping self-perception. This study highlights the need for comprehensive health interventions that integrate media literacy and support psychosocial well-being to further promote positive active lifestyles and body image among Indonesian adolescents.